Development of design and methods for soil directional thermostabilizer simulation - V. A. Maksimenko; V. V. Maksimenko; A. Zh. Shirazhiev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
This article is devoted to the study of the directional thermostabilizer efficiency. A parametric analysis determining the freezing radius on the central angle of the evaporation zone active surface dependence is performed. The frost halo results comparison, that is obtained in the ANSYS environment made around a symmetric and directional action thermostabilizer